Macroevolutionary Patterns of Sexual Size Dimorphism Among African Tree Frogs (Family: Hyperoliidae). (28th June 2020) - Portik, Daniel M; Blackburn, David C; McGuire, Jimmy A
Abstract: Sexual size dimorphism (SSD) is shaped by multiple selective forces that drive the evolution of sex-specific body size, resulting in male or female-biased SSD. Stronger selection on one sex can result in an allometric body size scaling relationship consistent with Rensch's rule or its converse. Anurans (frogs and toads) generally display female-biased SSD, but there is variation across clades and the mechanisms driving the evolution of SSD remain poorly understood. We investigated these topics in a diverse family of African treefrogs (Hyperoliidae). Hyperoliids display traits considered rare among amphibians, including sexual dichromatism and protogynous sex change. Using phylogenetic comparative methods, we tested if adult ecology, sexual dichromatism, and sex change were predictors of body size or SSD. We also tested whether hyperoliids displayed allometric interspecific body size scaling relationships. We found a majority of hyperoliid taxa display female-biased SSD, but that adult ecology and sexual dichromatism are poor predictors of sex-specific body size and SSD. Regardless of the groupings analyzed (partitioned by clades or traits), we found support for isometric body size scaling. However, we found that sex change is a significant predictor of SSD variation. Species in the Hyperolius viridiflavus complex, which putatively display this trait, show a significant reduction in SSD and are frequently sexually monomorphic in size. Although protogynous sex change needs to be validated for several of these species, we tentatively propose this trait is a novel mechanism influencing anuran body size evolution. Beyond this association, additional factors that shape the evolution of anuran body size and SSD remain elusive.